Monitoring of archaeological sites submerged in shallow waters using Earth observation - Themistocleous, Kyriacos; Abate, Dante; Kalogirou, Eleftheria; Krauss, Thomas (My University, 2024)
Archaeological sites that are submerged in shallow waters are subject to various environmental threats, including anthropogenic factors, climate change and environmental conditions. Due to their archaeological significance, they are vulnerable to extreme risks from deterioration due to land deformation, flooding, acid rain, erosion, and man-made hazards like illegal excavations and tourist activities. Such threats not only endanger the structural integrity of these monuments, but they also may cause total destruction, and loss of cultural heritage and history. This paper explores the capabilities of using Earth observation and aerial images and the capabilities of satellite-based remote sensing techniques for monitoring cultural heritage sites under shallow water conditions. The processing and analysis of Earth observation time series images provide information about the site's condition over time, enabling the detection of subtle changes that might be unnoticed with conventional methods. The case study focuses on the submerged port of Amathous archaeological site along the coast of Cyprus. The site's unique geographical and historical characteristics make it an exemplary model for applying advanced remote sensing technologies. By integrating various Earth observation satellite images with aerial imagery, the study aims to examine a methodology for the monitoring of underwater cultural heritage sites. This approach provides an understanding of the impacts of climate change as well as the human impact of various activities that affect the coastlines of cultural heritage sites and also provides a tool for developing proactive measures to safeguard heritage assets.
Keywords: Earth Observation; remote sensing; cultural heritage; Underwater Archaeology; Amathous; Submerged Sites